Prenatal diagnosis of hypospadias with 2-dimensional and 3-dimensional ultrasonography - Li, Xiaohua (Sci Rep, 2019)
To compare the prenatal diagnostic performance as well as appearance of ultrasonic details between 2-dimensional ultrasonography (2DUS) combined with 3-dimensional ultrasonography (3DUS) and 2DUS alone for hypospadias. A total of 47 fetuses were enrolled and examined by 2DUS and then 3DUS. Postnatal follow-up data were obtained and 28 cases were confirmed of hypospadias. Although not statistically significant, there was a trend toward higher AUC (0.85 vs. 0.76; p = 0.08), ACC (85.1 vs. 76.6%; p = 0.22), SEN (85.7 vs. 78.6%; p = 0.63), and SPE (84.2 vs. 73.7%; p = 0.50) for 2DUS combined with 3DUS compared with 2DUS alone. The agreement between both methods was moderate [kappa = 0.592]. Both modalities showed accurately the short penis and blunt tip of the penis. 2DUS in combination with 3DUS showed more cases in other detailed features, such as “chordee”, a “hooded” incomplete prepuce, and so on. Overall 2DUS combined with 3DUS showed a trend toward higher performance compared with 2DUS alone for the diagnosis of hypospadias, although the difference was not statistically significant. 3DUS is a useful complement for 2DUS in the diagnosis of fetal hypospadias and may provide more detailed information related to its diagnosis and prognosis.